2000
DOI: 10.1038/35005072
|View full text |Cite
|
Sign up to set email alerts
|

Soil pathogens and spatial patterns of seedling mortality in a temperate tree

Abstract: The Janzen-Connell hypothesis proposes that host-specific, distance- and/or density-dependent predators and herbivores maintain high tree diversity in tropical forests. Negative feedback between plant and soil communities could be a more effective mechanism promoting species coexistence because soil pathogens can increase rapidly in the presence of their host, causing conditions unfavourable for local conspecific recruitment. Here we show that a soil pathogen leads to patterns of seedling mortality in a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
851
5
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 814 publications
(901 citation statements)
references
References 26 publications
44
851
5
1
Order By: Relevance
“…Plant traits commonly show a phylogenetic signal, including the ones that are important in plant–enemy interactions, where close relatives are more likely to have similar traits (Agrawal, 2007), and are thereby susceptible to colonization by closely related pathogens. Due to their limited dispersal ability, initial colonization of fungi is most likely to occur on spatially associated hosts (e.g., Packer & Clay, 2000). Closely related tree species may also favor similar environmental conditions such as light and soil moisture (Emerson & Gillespie, 2008), which could facilitate the growth and reproduction of some closely related fungi that also prefer the same environments (Horn, Caruso, Verbruggen, Rillig, & Hempel, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant traits commonly show a phylogenetic signal, including the ones that are important in plant–enemy interactions, where close relatives are more likely to have similar traits (Agrawal, 2007), and are thereby susceptible to colonization by closely related pathogens. Due to their limited dispersal ability, initial colonization of fungi is most likely to occur on spatially associated hosts (e.g., Packer & Clay, 2000). Closely related tree species may also favor similar environmental conditions such as light and soil moisture (Emerson & Gillespie, 2008), which could facilitate the growth and reproduction of some closely related fungi that also prefer the same environments (Horn, Caruso, Verbruggen, Rillig, & Hempel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For these mechanisms to help maintain species diversity, local host specificity or selectivity of the enemies for host species is required, and as such, knowledge of the host range of pathogens is fundamental to understanding their impacts. However, most studies of pathogens in such feedback systems have either focused on specific plant–pathogen interactions (e.g., Gilbert, Hubbell, & Foster, 1994; Packer & Clay, 2000) or have treated the whole pathogen community as a black box without identifying its composition and diversity (e.g., Bever, 1994; Klironomos, 2002; Liu et al., 2012; Mangan et al., 2010; Petermann, Fergus, Turnbull, & Schmid, 2008; Spear, Coley, & Kursar, 2015). Neither approach provides a clear picture of how diverse sets of interacting host and pathogen species shape community diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Since soil pathogens can reduce survival of tree seedlings (Augspurger 1984;Packer and Clay 2000) and reduce the abundance of trees relative to herbaceous vegetation (Weste 1986), it is possible that pathogenic infection rates differed between the non-indigenous and native grass subplots. At Cedar Creek, Johnson et al (1991) found that different grass species support different the communities of vesicular-arbuscular mycorrhizal (VAM) fungi, and, in particular, that VAM fungi communities differed between garden plots composed of Schizachyrium scoparium and Poa pratensis, respectively (Johnson et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These stages of growth are important because they are the most numerous, and during these stages mortality can be very high. It now seems probable that intense mortality at the seed-to-seedling transition is frequently caused by plant pathogens, particularly Oomycota, which cause damping-off diseases in young seedlings (Augspurger 1983a(Augspurger ,b, 1990Dobson & Crawley 1994;Gilbert et al 1994;Gilbert & Hubbell 1996;Packer & Clay 2000;Gilbert 2005). In the rest of this paper, we will concentrate on the effects of pathogens on coexistence through seedling mortality, although many of the points that we make are equally applicable to other natural enemies.…”
Section: Introductionmentioning
confidence: 99%